2015
DOI: 10.1177/0734242x15586476
|View full text |Cite
|
Sign up to set email alerts
|

Refuse derived fuel (RDF) plasma torch gasification as a feasible route to produce low environmental impact syngas for the cement industry

Abstract: Plasma torch gasification (PTG) is currently researched as a technology for solid waste recovery. However, scientific studies based on evaluating its environmental implications considering the life cycle assessment (LCA) methodology are lacking. Therefore, this work is focused on comparing the environmental effect of the emissions of syngas combustion produced by refuse derived fuel (RDF) and PTG as alternative fuels, with that related to fossil fuel combustion in the cement industry. To obtain real data, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar to other technologies previously analysed in literature [55] which evidence the high relevance of location in the environmental impact associated to the processes, the result obtained in this study confirmed that the country mix existing is also an important variable for the technology analysed in this paper.…”
Section: Lca Environmental Resultssupporting
confidence: 88%
“…Similar to other technologies previously analysed in literature [55] which evidence the high relevance of location in the environmental impact associated to the processes, the result obtained in this study confirmed that the country mix existing is also an important variable for the technology analysed in this paper.…”
Section: Lca Environmental Resultssupporting
confidence: 88%
“…In this sense, a promising route to attain reliable environmental impact and cost reduction of supply chain materials is based on considering circular economy approaches [2]. This concept is already applied to other energy systems and manufacturing processes, where the reuse of energy flows [3], materials employing waste converted into by-products [4] or energy [5] are deeply analysed, to avoid virgin material consumptions. Some insights regarding the environmental issues of battery recycling are already provided but, results are mostly based on different reference scenarios, which make it difficult to perform comparisons.…”
Section: Introductionmentioning
confidence: 99%